Unified approach to bi-directional non-back drivable roller clutch design. (October 2017) - Controzzi, Marco; Bassi Luciani, Lorenzo; Montagnani, Federico
Highlights: Non-back drivability may be implemented exploiting the wedge phenomenon. A set of equations is presented to optimize the design of non-back drivable clutch. The paper includes step-by-step procedure useful in the design of these clutches. Abstract: A non-back drivable mechanism (transmission or clutches) is a device able to transmit torques from its input to the output axis and vice-versa to lock torques applied to its output. These devices are widely used in robotic, mechatronic systems and prosthetics in order to lock joints or to physically engage/disengage transmission axes. An efficient way to implement non-back drivability is to exploit the wedge phenomenon that occurs to rolling elements when they are compressed between circular and cam surfaces. The current literature describing such mechanisms and underlying equations is rather scattered and incomplete. In this paper, a relevant set of equations is presented to optimize their design, which is of particular interest in prosthetics to minimize weight of limbs. The conceptual framework and the general design are described. The relationship between the locking torque and the properties of the components are then derived. Moreover, the sources and effects of tolerance and of operational conditions are introduced. The contact pressures, the input torque required to unlock the clutch, the critical torque and the input backlash are finally analyzed. The final part of the paper is devoted to a step-by-step procedure useful in the design of non-back drivable roller clutches.